Optimization of Cathode/Anode Electrode Materials for High Performance Lithium-ion Batteries - (:unkn) unknown (My University, 2021)
Lithium-ion batteries (LIBs) have been widely used in various devices such as portable devices, communication systems, and electric vehicles (EVs). In this dissertation, towards building LIBs with enhanced energy density and improved performance, Ni-rich cathode and Si-based anode are selected as the electrodes. The performance of LIBs is improved through optimization on both cathode and anode material. Ni-rich layered transition metal oxide with dual gradient on both primary and secondary particles was successfully designed and synthesized through introducing Ni-based metal-organic framework (Ni-MOF) to the coprecipitation of the precursor. During the calcination process, the presence of organic components of Ni-MOFs promotes the formation of reduced Ni oxidation state, leading to the formation of self-induced cation mixing layer with stable rock salt phase on the surface of primary particles. It can successfully increase the structural stability through inhibiting the generation of internal cracks caused by the internal strain and phase transition within primary particles during cycling process. The metallic components from Ni-MOFs in the core lead to the formation of Ni concentration gradient within secondary particles. As results, a greatly improved electro-chemo-mechanical stability was achieved, which contributed to the enhanced battery capacity retention upon long cycling. At the same time, to overcome the disadvantages of Si-based anode material, including huge volume change, poor cycling stability, and low conductivity, micro-sized AlSi alloy was used to form the Si skeleton with an ultra-thin (
Keywords: concentration gradient; lithium-ion batteries; mass production; MOF; Ni-rich cathode; Silicon